Pemberdayaan Kader Kesehatan Pada Deteksi Dini Flat Foot di Posyandu Desa Manggung Kecamatan Ngemplak Kabupaten Boyolali - Alfan Zubaidi; Anissa Septiani (Health Care : Journal of Community Service, 2026)
Flat foot, or pes planus, is a foot deformity closely associated with the incidence of injuries to the lower extremities and is experienced by millions of people worldwide. The prevalence of flat foot reaches 25% of the general population. The aim of this community service program is to empower the role of health cadres in the early detection of flat foot at the Integrated Health Post (Posyandu) of Manggung Village, Ngemplak District, Boyolali Regency. The method employed includes educational outreach to all Posyandu cadres, encompassing the wet footprint test, Clarke's angle measurement, gait assessment, and footwear evaluation. A total of 14 Posyandu groups were involved as subjects of the program. The expected outcomes are an improvement in the cadres' knowledge and skills in independently detecting suspected flat foot in children under the age of five.